A Review of “Aware of the Whale: An Attempt to Understand the Dichotomy of Structure-Agency” by Birsen Banu Okutan - Necmiye Durmuş (Darulfunun Ilahiyat)
Birsen Banu Okutan. Balinanın Farkında: Yapı-Fail Dikotomisini Anlama Girişimi (Ankara: Tezkire Yayınları, 2023) ISBN: 9786059835473